The secret supper - Sierra, Javier, 1971-; Manguel, Alberto (New York : Atria Books, 2006)
Sent to oversee the completion of Da Vinci's "The Last Supper," Dominican inquisitor Fray Agustin Leyre investigates the artist's omission of key elements and use of symbolic imagery, which suggests that there is a coded message in the painting.
Translation of: La cena secreta.
Illustrations on lining papers.
Keywords: Leonardo, -- da Vinci, -- 1452-1519. -- Fiction; c -- e Vinci,d -- Romans, nouvelles, etc